Voices of surgical wards nurses on barriers hindering acute post-operative pain management at Tshwane municipality, South Africa - Nnene Melia Makou; Melitah Molatelo Rasweswe; Ramadimetja Shirley Mooa (PLoS ONE, 2025)
Introduction and background Acute pain is expected following a surgery, but it is often inadequately managed by health care providers. However, little is known about the barriers that hinder acute post-operative pain management among surgical wards nurses. Objective Uncovering barriers that hinder the surgical wards nurses to manage acute post-operative pain at the selected public hospital in Tshwane municipality, Gauteng Province, South Africa. Methods This study utilized a qualitative explorative, descriptive, and contextual research design. Individual semi-structured interviews were conducted from a purposive sampling of 13 professional nurses. Data collected were audio recorded and transcribed verbatim by the first author. Data were analysed using thematic data analysis, which led to the emergence of themes and sub-themes. An independent co-coder assisted with data analysis. Findings The barriers described by the participants include: 1) Organisational/ management related barriers; 2) Personnel related barriers, which were discussed as shortage of nurses, inadequate skill competency to manage acute post-operative pain, and interprofessional communication; and 3) Patient related barriers. Conclusion This paper comes to the conclusion that, due to a number of stated barriers or obstacles, the nurses employed in the surgical wards of the selected hospital in South Africa are not adequately managing the acute post-operative pain. As a result, hospital management must devise practical solutions to the stated obstacles.